2017
DOI: 10.1093/eurpub/ckx064
|View full text |Cite
|
Sign up to set email alerts
|

Do perceived barriers to clinical presentation affect anticipated time to presenting with cancer symptoms: an ICBP study

Abstract: Perceived barriers to help-seeking have a role in delaying GP presentation. Early diagnosis campaigns should address emotional and practical barriers that reduce early presentation with potential cancer symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…A significant contributor to disease burden and mortality in low- and middle-income countries is late presentation for diagnosis and treatment [ 43 , 44 ]. Difficulties to access treatment, financial burden of medical care and negative beliefs associated with a cancer diagnosis might all contribute to a delay in diagnosis [ 18 , 27 , 43 , 45 47 ]. Negative beliefs may be fueled by shared local experiences as well as poor knowledge of treatment options and outcomes [ 18 , 45 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…A significant contributor to disease burden and mortality in low- and middle-income countries is late presentation for diagnosis and treatment [ 43 , 44 ]. Difficulties to access treatment, financial burden of medical care and negative beliefs associated with a cancer diagnosis might all contribute to a delay in diagnosis [ 18 , 27 , 43 , 45 47 ]. Negative beliefs may be fueled by shared local experiences as well as poor knowledge of treatment options and outcomes [ 18 , 45 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Instruments used to measure symptom knowledge included the Cancer Awareness Measure (CAM) Robb et al, 2009;Waller et al, 2009), the Awareness and Beliefs about Cancer (ABC) measure (Donnelly et al, 2017), the Knowledge of Cancer Warning Signs Inventory (KCWSI) , the Identity subscale of the Illness Perception Questionnaire (IPQ) , and other diverse scales, including self-generated items. All but one study measured objective symptom knowledge (correct vs. incorrect recognition of symptoms as potentially indicative of cancer); the remaining study measured self-reported symptom knowledge before diagnosis .…”
Section: Symptom Knowledge (K=31)mentioning
confidence: 99%
“…The remaining studies measured beliefs about the curability of cancer or the benefits of early detection and treatment. Among the scales used were the Awareness and Beliefs about Cancer (ABC) measure (Donnelly et al, 2017), items from the Cure/control subscale from the Illness Perception Questionnaire , the Power Fatalism Inventory , and selfgenerated items. For the purpose of analyses, the results were expressed such that a higher score reflected more positive beliefs (one-point change in the used scale).…”
Section: Cancer Beliefs (K=18)mentioning
confidence: 99%
“…Factors such as access to health care and education also play a part in the decision to initiate help-seeking. Barriers such as financial concerns, lack of information online, perceived poor quality of care, negative influence of relatives, being too busy, fear and embarrassment appear to merit attention in terms of improving understanding about anticipated time to help-seeking for cancer [37][38][39].…”
Section: Discussionmentioning
confidence: 99%